Significant Differences in Personality Styles of Securely and Insecurely Attached Psychotherapists: Data, Reflections and Implications - Peter, Burkhard; Böbel, Eva (Frontiers in Psychology, 2020)
This is a contribution to the research on the therapist variable aiming to improve effectiveness of psychotherapy. It is shown that attachment styles shape personality styles of psychotherapists in a favorable or unfavorable manner. Data on personality (PSDI) and attachment (RSQ) styles was collected from 430 psychological psychotherapists of the DACH countries using an online survey. The 88 insecurely attached psychotherapists differed significantly from their 342 securely attached colleagues in 9 of 14 personality styles: They were – even though well within normal range – more paranoid, borderline, schizoid, dependent, negativistic, self-sacrificing, avoidant, and depressive, as well as less optimistic. This corresponds to results of other researchers. Data regarding their effectiveness was not available. It is argued that a secure attachment style predispose to be a good psychotherapist. Yet, insecurely attached psychotherapists possibly compensate their adverse traits through self-therapy, continuous education, and supervision.